PENGELOLAAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) DI KECAMATAN LONG PAHANGAI KABUPATEN MAHAKAM ULU - Suyati, Suyati; Jauchar B; Niken Nurmiyati (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the management of Solar Power Plants (PLTS) in Long Pahangai District, Mahakam Ulu Regency, East Kalimantan. The background of this research is the significant challenges related to energy access in Indonesia’s border areas, where infrastructure is limited and operational costs for conventional electricity provision are high. The research methodology used is a descriptive qualitative approach with a case study, which allows for an in-depth understanding of the implementation of renewable energy technology. The findings of the study show that the government subsidy policy for the installation of PLTS has a positive impact on increasing access to renewable energy, which in turn has led to improvements in the social and economic activities of the local community. However, limitations in human resources (HR), geographical challenges, and extreme weather conditions have been significant barriers in the management of PLTS. In addition, ineffective coordination between agencies has hindered the implementation of the program. The discussion reveals that to overcome these challenges, there is a need for increased technical training for the community, the use of communication technology to address geographical barriers, and improved coordination among the involved agencies. In conclusion, although PLTS offers long-term benefits, better collaboration between the government and the community is crucial to overcome the existing challenges, ensuring that the program runs effectively and sustainably